2012
DOI: 10.1091/mbc.e12-04-0331
|View full text |Cite
|
Sign up to set email alerts
|

Sub1 associates with Spt5 and influences RNA polymerase II transcription elongation rate

Abstract: The transcriptional coactivator Sub1 is a functional component of the PIC implicated in several steps of mRNA metabolism. Sub1 directly and specifically influences the transcription elongation rate by an interaction with the elongation factor Spt5. The results provide a novel mechanistic insight into the process of elongation by RNAPII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(79 citation statements)
references
References 80 publications
17
62
0
Order By: Relevance
“…These genetic data prompted us to hypothesize that the sub1 ∆ strain might exhibit a slow elongation rate, which was confirmed by Garcia, et al while the work by Braberg, et al was under review: RNAPII elongates slowly on the GAL1 gene in the absence of SUB1 51 . Consistent with our predictions, the sub1 ∆ strain exhibited improved splicing at a large number of genes, similar to what is observed in slow RNAPII mutant strains.…”
Section: How Might Kinetic Coupling Occur In S Cerevisiae?supporting
confidence: 87%
“…These genetic data prompted us to hypothesize that the sub1 ∆ strain might exhibit a slow elongation rate, which was confirmed by Garcia, et al while the work by Braberg, et al was under review: RNAPII elongates slowly on the GAL1 gene in the absence of SUB1 51 . Consistent with our predictions, the sub1 ∆ strain exhibited improved splicing at a large number of genes, similar to what is observed in slow RNAPII mutant strains.…”
Section: How Might Kinetic Coupling Occur In S Cerevisiae?supporting
confidence: 87%
“…The epistatic relationships between fast RNAPII alleles and sub1Δ suggest that Sub1 activity may be bypassed when RNAPII catalytic activity is increased. Collectively, our data indicate that Sub1 plays a direct role in transcriptional initiation and influences mRNA splicing, possibly via its effect on elongation (García et al, 2012). …”
Section: Discussionmentioning
confidence: 78%
“…We focused on genes that behaved as positively acting factors and observed that sub1Δ had the strongest pattern in this regard. Interestingly, previous evidence has implicated Sub1 as a positive factor in in vitro transcription assays (reviewed in Conesa and Acker, 2010), as well as in vivo (García et al, 2012). The genetic relationships from the pE-MAP were confirmed using standard growth assays in which sub1Δ exacerbated slow RNAPII alleles (Figure 7B) and partially suppressed fast RNAPII alleles (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Sub1 interacts with RNA polymerase II 24,25 and III 26 and plays an essential regulatory role in transcription initiation, elongation, and mRNA 3’-end formation 24,27,28 . We therefore tested whether Sub1 can bind to a G4 region on chromosomal DNA in vivo .…”
mentioning
confidence: 99%